2004
DOI: 10.1301/nr.2004.aug.295-306
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients for Cognitive Development in School-aged Children

Abstract: This review considers the research to date on the role of nutrition in cognitive development in children, with a particular emphasis on the relatively neglected post-infancy period. Undernutrition and deficiencies of iodine, iron, and folate are all important for the development of the brain and the emergent cognitive functions, and there is some evidence to suggest that zinc, vitamin B12, and omega-3 polyunsaturated fatty acids may also be important. Considerations for future research include a focus on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 81 publications
1
66
1
Order By: Relevance
“…1,2 Part of the reason for this lack of information is undoubtedly that the most widespread pesticide exposures occur in developing countries, where epidemiological studies may be difficult to carry out and where malnutrition and other potential confounders may compromise the results. On the other hand, extensive evidence has been gathered on the neurobehavioral consequences of malnutrition and stunting, [4][5][6]19,54 but these studies have not included pesticide exposure as a relevant cofactor that could impact on child development.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Part of the reason for this lack of information is undoubtedly that the most widespread pesticide exposures occur in developing countries, where epidemiological studies may be difficult to carry out and where malnutrition and other potential confounders may compromise the results. On the other hand, extensive evidence has been gathered on the neurobehavioral consequences of malnutrition and stunting, [4][5][6]19,54 but these studies have not included pesticide exposure as a relevant cofactor that could impact on child development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the maturation of specific brain areas during childhood is associated with development of specific cognitive functions such as language, reading, and memory (Nagy et al, 2004;Deutsch et al, 2005;Giedd et al, 2010). The development of the frontal lobes, which are believed to control higher cognitive functions (including planning, sequencing and self-regulation), appears to occur in growth spurts during the first 2 years of life, and then again between 7 and 9 years of age and also around 15 years of age (Thatcher, 1991;Bryan et al, 2004). The development of some subcortical structures including the basal ganglia, amygdala, and hippocampus (which are also centrally involved in some mediating higher cognitive functions, including memory, executive functions, and emotion) also continues until late adolescence.…”
Section: Brain Development In Humansmentioning
confidence: 99%
“…Overall, the research evidence suggests that cognitive development is strongly connected with micro and macro-anatomical changes which take place throughout childhood (Levitt, 2003;Herlenius and Lagercrantz, 2004;Ghosh et al, 2010). Individual brain development follows a genetic program which is influenced by environmental factors including nutrition (Bryan et al, 2004;Toga et al, 2006;Giedd et al, 2010). Environmental influences may modify gene expression through epigenetic mechanisms, whereby gene function is altered through the processes of DNA methylation, histone modification and the modulating effect of non-coding RNAs, without the alteration of the gene sequence per se.…”
Section: Brain Development In Humansmentioning
confidence: 99%
“…This index ranges from 0 to 20, where 0 represents the lowest and 20 the highest socioeconomic status code. The socioeconomic status variable was used either as a continuous variable or as a discrete one (by three categories: 0-10, 11-14, and [15][16][17][18][19][20].…”
Section: Study Variablesmentioning
confidence: 99%
“…Postnatal exposure of normal infants to a damaging environment, including nutritional deficiencies especially during the first year of life, may have long-lasting effects similar to those observed following intrauterine exposure (12,(17)(18)(19). Indeed, such long-term developmental consequences have been associated with deficiencies in several vitamins in childhood, including vitamin B 12 (20). It is not clear whether mild or subclinical B 1 deficiency in infancy, which theoretically could cause slight Articles Ornoy et al…”
mentioning
confidence: 99%